Aplicação de planejamento fatorial no estudo de degradação forçada em meio ácido da matéria-prima de apixabana - Rodrigues, Igor Natã Fagundes (2024)
This work aimed to apply the full factorial design approach, including central and axial points, to assess the influence of temperature, degradant concentration and time factors on the acid degradation reaction of the apixaban raw material molecule. Through the statistical analysis methodology employed in evaluating the experimental results, using ANOVA, response surface plots, and desirability function, it was found that test 8 (HCl 1 mol L-1, 60 °C, and 24 h) yielded the highest results for content decay, impurity formation, and mass balance close to 100%. It was also possible to generate a Design Space plot, providing a visualization of the working space where factor conditions are ideal for the acid degradation of the apixaban PA.